(3Yjhf GdJhGQjNs - (3eMeO Hf TGcQ Hf CMeO Hf YHO GdQMef GdcJHj GdOGQGfqj GdOeTbqj, UdGM GdOjf , GHf TGcQ J (B764 (3g` s ((3eMeO Hf eMeO Hf eadM s)
(3ChdgG (B:s
(3jHOC ef SfI (B218(3g` s
(3BNQgG (B:s
(3jfJgi Edi SfI (B250(3g` s
(3fSNI KGefIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B156 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B61s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B48 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B219 s
Keywords: (3GdJGQjNs